Education Level and Mating Success: Undercover on Tinder - Brecht Neyt; Sarah Vandenbulcke; Stijn Baert (Institute of Labor Economics (IZA), 2018)
In this study, we examine the impact of an individual's education level on her/his mating success by means of a field experiment on the mobile dating app Tinder, using a sample of 3,600 profile evaluations. In line with previous studies from the field of evolutionary psychology, our results indicate a heterogeneous effect of education level by gender: while females strongly prefer a highly educated potential partner, we cannot accept this hypothesis for males. Additionally, in contrast with previous literature on partner choice in an offline context and on classic online dating websites, we do not find any evidence for educational assortative mating, i.e. preferring a partner with a similar education level, on mobile dating apps such as Tinder. We argue that this is due to our research design, which allows us to examine actual (instead of stated) mate preferences in a dating market without search frictions and social frictions.
Keywords: C93; I26; J12; 330; returns to education; mating success; assortative mating; dating apps; Tinder